2018
DOI: 10.1007/s12010-018-2789-0
|View full text |Cite
|
Sign up to set email alerts
|

Activity Essential Residue Analysis of Taxoid 10β-O-Acetyl Transferase for Enzymatic Synthesis of Baccatin

Abstract: Taxoid 10β-O-acetyl transferase (DBAT) is a key enzyme in the biosynthesis of the famous anticancer drug paclitaxel, which catalyses the formation of baccatin III from 10-deacetylbaccatin III (10-DAB). However, the activity essential residues of the enzyme are still unknown, and the acylation mechanism from its natural substrate 10-deacetylbaccatin III and acetyl CoA to baccatin III remains unclear. In this study, the homology modelling, molecular docking, site-directed mutagenesis, and kinetic parameter deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…There were 13 mutational “hotspots” (Pro37, Val39, Asn42, Ile43, Ser122, His162, His123, Glu124, Ser159, Leu168, Gly171, Ile175, and Ser189) in the solvent channel ( Figure 2 ) chosen for site-directed mutagenesis. As the residue His162 was proved to be the key catalytic site of DBAT in our previous study ( You et al, 2018 ). When the residue His162 was mutated to other amino acids, DBAT will completely lose its activity.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…There were 13 mutational “hotspots” (Pro37, Val39, Asn42, Ile43, Ser122, His162, His123, Glu124, Ser159, Leu168, Gly171, Ile175, and Ser189) in the solvent channel ( Figure 2 ) chosen for site-directed mutagenesis. As the residue His162 was proved to be the key catalytic site of DBAT in our previous study ( You et al, 2018 ). When the residue His162 was mutated to other amino acids, DBAT will completely lose its activity.…”
Section: Resultsmentioning
confidence: 86%
“…Since the dbat gene was successfully cloned over two decades, research on DBAT has mainly focused on (i) cloning and heterologous expression of DBAT from different species ( Guo et al, 2007 ; Han et al, 2014 ; Sah et al, 2019 ), (ii) the regional specificity and substrate diversity of DBAT ( Loncaric et al, 2006 , 2007 ), and (iii) the exploration of the unnatural substrate ( Li et al, 2017 ; Lin et al, 2018 ; You et al, 2018 , 2019 ; Huang et al, 2020 ). However, research on the thermal stability of DBAT has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, one unigene encoding TS and three unigenes encoding TAT were identified, and they predominantly expressed in T. yunnanensis. DBAT, another rate-limiting enzyme, catalyzes the formation of baccatin III from 10-deacetylbaccatin III [44]. BAPT is responsible for the transfer of a C13-side chain to baccatin III [45].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 72 ] generated a three-dimensional structure of DBAT and identified its active site using alanine scanning, and designed a double DBAT mutant (DBAT G38R/F301V) with a catalytic efficiency approximately six times higher than that of the DBAT wildtype (WT), which improved an in vitro one-pot conversion of 7-b-xylosyl-10-deacetyltaxol to taxol. Moreover, the activity essential residues of the enzyme DBAT, and the acylation mechanism from its natural substrate 10-DAB and acetyl CoA to baccatin III were investigated by You et al [ 74 ]. Among them, residues H162, D166 and R363, located in the catalytic pocket of the enzyme, were important for DBAT activity; and residues S31 and D34 from motif SXXD, D372 and G376 from motif DFGWG were important for acylation.…”
Section: Acylation Reactions Mediated By Taxus Actsmentioning
confidence: 99%